Glossogyne tenuifolia (Hsiang-ju) extract suppresses T cell activation by inhibiting activation of c-Jun N-terminal kinase - Jer-Yiing Houng; Tzong-Shyuan Tai; Shu-Ching Hsu; Hsia-Fen Hsu; Tzann-Shun Hwang; Chih-Jiun Lin; Li-Wen Fang (BMC, 2017)
Abstract Background Glossogyne tenuifolia (GT) (Hsiang-ju) is a Chinese herbal medicine previously exhibited an anti-inflammatory activity. This study aimed to investigate the effect of GT ethanol extract (GTE) on T cell-mediated adaptive immunity. Methods Human peripheral blood mononuclear cells (PBMCs) and Jurkat T cells were activated by phytohemagglutinin in the presence of various doses (3.13-50 μg/mL) of GTE. The effect of GTE on T cell activation was examined by a proliferation assay of activated PBMCs and the level of the activation marker CD69 on the surface of activated Jurkat T cells. Apoptosis was determined by propidium iodide staining in hypotonic solution. Signaling pathway molecules were assessed by western blotting. Results Glossogyne tenuifolia ethanol extract was demonstrated to inhibit T cell activation, not only in the proliferation of human PBMCs at the concentrations of 12.5, 25 and 50 μg/mL (P = 0.0118, 0.0030 and 0.0021) but also in the CD69 expression in Jurkat cells, which was not due to the cytotoxicity of GTE. The presence of GTE did not change the activity of nuclear factor kappa-light-chain-enhancer of activated B cells or extracellular signal-regulated kinase upon T cell activation. In addition, GTE significantly reduced activation of c-Jun N-terminal kinase (JNK) (P = 0.0167) and p38 (P = 0.0278). Furthermore, decreased JNK activation mediated the preventive effect of GTE on T cell activation-induced cell death (AICD). Conclusion Glossogyne tenuifolia ethanol extract inhibited T cell activation of Jurkat cells and freshly prepared human PBMCs due to suppression of JNK activity. Furthermore, GTE inhibited AICD by blocking prolonged JNK phosphorylation in activated T cells. Taken together, the anti-inflammatory effects exerted by GTE were mediated via suppression of JNK phosphorylation in T cell activation.